Slip Plane in the Ether V (Global Journal of Science Frontier Research, 2020)
In this paper, we consider the Ether as a partial crystal material. We consider the natural slip plan that is, for fluorocarbons, a natural break points that lines up with AT Math. We also consider the phase diagram that shows that the crystal is triclinic. These calculations show that the Ether is modelling as the partial crystallization of polytetrafluorethylene.
Keywords: face centered cube; crystallization; triclinic crystal